Simple and Efficient Synthesis of Gold Nanoclusters and Their Performance as Solid Contact of Ion Selective Electrode. (20th December 2016) - Xu, Jianan; Jia, Fei; Li, Fenghua; An, Qingbo; Gan, Shiyu; Zhang, Qixian; Ivaska, Ari; Niu, Li
Graphical abstract: Abstract: Gold nanoclusters are ideal materials as solid transducer in all-solid-state ion-selective electrodes (ISEs) due to their high hydrophobicity, excellent ion-to-electron transduction, high specific capacitance and outstanding chemical stability. In this paper, monolayer-protected gold nanoclusters (MPCs) were synthesized by a simple one-phase method requiring a relatively short reaction time with high yield (60%). Transmittance electronic microscopy (TEM) and atomic-force microscopy (AFM) were used to characterize the morphology of MPCs. The composition of MPCs was studied by UV–vis spectrometry, Matrix-assisted laser desorption ionization (MALDI) mass spectrometry, X-ray diffraction (XRD) measurement and X-ray photoelectron spectroscopy (XPS) measurements. The performance of MPCs based ISEs was thoroughly characterized by electrochemical impedance, electromotive force and chronopotentiometry measurement. Comparison with the performance of ISE with other signal transducing materials such as conductive polymer, carbon nanotube, graphene and fullerene, the MPCs based ISEs have higher potential st ability and reproducibility, lower detection limit, longer operating life (one year) and higher anti-interference ability.